2022
DOI: 10.1186/s12889-022-14753-x
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of weak grip strength and fall: a study based on the China Health and Retirement Longitudinal Study (CHARLS)

Abstract: Background Fall is a major cause of mortality and cause a significant burden on the healthcare system and economic system. Weak grip strength signifies impaired function. Older people with weak grip strength are at a higher risk of death. China has the largest ageing population in the world today. This study aims to analyze the factors contributing to weak grip strength and fall among Chinese. Methods This study analyzed data from the 2011 baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Some studies have found that knee and/or lower back pain coupled with other painful sites are associated with increased risk of falls [10,13,14]. In our previous study, grip strength was a risk factor of falls [15]. It should be noted that there are limited studies exploring the association between musculoskeletal pain and the risk of falls, most of which were performed in Caucasian populations.…”
Section: Introductionmentioning
confidence: 78%
“…Some studies have found that knee and/or lower back pain coupled with other painful sites are associated with increased risk of falls [10,13,14]. In our previous study, grip strength was a risk factor of falls [15]. It should be noted that there are limited studies exploring the association between musculoskeletal pain and the risk of falls, most of which were performed in Caucasian populations.…”
Section: Introductionmentioning
confidence: 78%
“…Muscle weakness is a significant risk factor for falls [8,29]. A low HGS is generally reported as an indicator of overall muscle strength [30] and does not only increase the fall risk of older adults [11] but also serves as a predictor of dynamic postural balance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Falls have various causes in older people, most notably decreased musculoskeletal function [5], such as muscle weakness. Prior research has consistently revealed a heightened likelihood of falls by individuals presenting with a diminished handgrip strength (HGS) [8][9][10][11]. For instance, in a longitudinal study conducted among residents of mainland China aged 45 years and older, weak grip strength was reported as a risk factor for falls [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, frailty often presents as a dysregulated immune response, exacerbating physical vulnerabilities such as diminished grip strength, an increased risk of falls, and a reduced healthy lifespan in older adults [ 7 , 8 , 9 , 10 , 11 ]. The dysregulation of CD4 + T cells has been shown to aggravate chronic proinflammatory cytokine production during aging [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%